Real‐time hybrid control of electrohydraulic active suspension. (13th June 2017) - Shaer, Bassel; Kenné, Jean‐Pierre; Kaddissi, Claude; Mintsa, Honorine Angue
Summary: Electrohydraulic actuators are an attractive choice for active suspension, because these systems provide a high power‐to‐weight ratio. However, their dynamics are highly nonlinear. In addition, the use of one simple controller for both position and force is complicated, because there is a compromise between them in the case of active suspension. Most existing controllers do not efficiently fulfill the requirements, because only one state variable is considered. In this paper, we address these problems by developing a new hybrid controller for both position and force and implementing it in a real‐time test bench. Our goal is to control the vertical position of the passenger seat while tracking the force transmitted to passengers and keeping it within tolerable and comfortable limits. Therefore, the proposed controller is a combination of two controllers. Its flexible structure redirects the control signal to control the proper controlled state variable. The real‐time results of the newly designed hybrid controller are compared with those obtained using a classical proportional integral derivative controller, because this is the most widely used controller in the industry. As expected, the proposed controller demonstrates better performance in real‐time operation. Copyright © 2017 John Wiley & Sons, Ltd.